2013
DOI: 10.3109/0886022x.2013.794682
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of epicardial adipose tissue in non-diabetic, non-hypertensive hemodialysis patients

Abstract: Turkey AbstractPurpose: It has been found out that the epicardial adipose tissue (EAT) measured by echocardiography is related with various metabolic parameters. Being accepted as the new cardiovascular risk indicator, there have been few studies on EAT in relation to the patients with end-stage renal failure. In our study, we aim to evaluate EAT and carotid intima media thickness (CIMT) in non-diabetic, non-hypertensive hemodialysis (HD) patients. Methods: Our study recruited 47 non-diabetic, non-hypertensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
3
2
1
Order By: Relevance
“…They found that stage IV and V patients had higher epicardial fatty vol-umes compared to the controls [28]. Despite this, Ozkurt et al showed that EFT was similar in CKD patients and controls [29]. In our study, we found that stage IV and V subjects had the higher EFT, which is consistent with a meta-analysis by Song et al [27].…”
Section: Discussionsupporting
confidence: 90%
“…They found that stage IV and V patients had higher epicardial fatty vol-umes compared to the controls [28]. Despite this, Ozkurt et al showed that EFT was similar in CKD patients and controls [29]. In our study, we found that stage IV and V subjects had the higher EFT, which is consistent with a meta-analysis by Song et al [27].…”
Section: Discussionsupporting
confidence: 90%
“…Some studies demonstrated an increase in EAT thickness by MSCT in patients with PD and HD, 8,9 while in another study, EAT thickness acquired by echocardiography in patients with HD was similar to control subjects. 29 In our study, we found that EAT thickness was higher in HD patients and was correlated with CIMT used for detecting early atherosclerosis, as similar to other studies. 16,30 Consistent with other studies, correlations between EAT thickness and cardiovascular risk factors (age, calcium) were also presented in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Until now, studies have reported conflicting results about EAT thickness in receiving HD and PD patients. Some studies demonstrated an increase in EAT thickness by MSCT in patients with PD and HD,while in another study, EAT thickness acquired by echocardiography in patients with HD was similar to control subjects . In our study, we found that EAT thickness was higher in HD patients and was correlated with CIMT used for detecting early atherosclerosis, as similar to other studies .…”
Section: Discussionsupporting
confidence: 89%
“…However, there are little data about the association of EAT and clinical parameters in an end‐stage renal disease (ESRD) population . Unfortunately, there are no data in the literature about EAT thickness of the Rtx patients in the post‐transplantation period.…”
mentioning
confidence: 99%